2020
DOI: 10.1055/a-1243-0092
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of lumen-apposing metal stents versus plastic stents to treat walled-off pancreatic necrosis: systematic review and meta-analysis

Abstract: Background and study aims Lumen-apposing metal stents (LAMS) are increasingly used for drainage of walled-off pancreatic necrosis (WON). Recent studies suggested greater adverse event (AE) rates with LAMS for WON. We conducted a systematic review and meta-analysis to compare the safety and efficacy of LAMS with double-pigtail plastic stents (DPPS) for endoscopic drainage of WON. The primary aim was to evaluate stent-related AEs. Methods In October 2019, we searched the Ovid (Embase, MEDLINE, Cochrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 61 publications
0
32
1
Order By: Relevance
“…AEs were further stratified according to time from index procedure (ie, early vs delayed) and according to severity of the AE, which are details that have been inconsistently reported in prior studies involving LAMS drainage for PFCs. 17 A recent multicenter retrospective study suggested that LAMS were found to be associated with higher rates of AEs when used for drainage of WON, but the rates of AEs observed in that study were notably higher than we observed in this study. 18 Another strength of the present study was that both radiologists who interpreted the preprocedural cross-sectional imaging studies and the endosonographer who interpreted EUS images captured during the index procedure were blinded to the patient's clinical outcome.…”
Section: Discussioncontrasting
confidence: 88%
“…AEs were further stratified according to time from index procedure (ie, early vs delayed) and according to severity of the AE, which are details that have been inconsistently reported in prior studies involving LAMS drainage for PFCs. 17 A recent multicenter retrospective study suggested that LAMS were found to be associated with higher rates of AEs when used for drainage of WON, but the rates of AEs observed in that study were notably higher than we observed in this study. 18 Another strength of the present study was that both radiologists who interpreted the preprocedural cross-sectional imaging studies and the endosonographer who interpreted EUS images captured during the index procedure were blinded to the patient's clinical outcome.…”
Section: Discussioncontrasting
confidence: 88%
“…At the same time, treatment courses of severe pancreatitis can be extremely protracted and often require specific gastroenterological competencies and close interdisciplinary collaboration with interventional radiological and surgical disciplines in the context of complication management [26]. This relates, for example, to the options of endoscopic necrosectomy via lumen-apposing metal stents (LAMS), radiological drainage, and surgical video-assisted necrosectomies [27,28]. Our study observed a total hospital mortality rate for AP of 2.85 %, which is in good agreement with previous studies from Germany [1,4] and other western countries [29,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Fully covered selfexpandable metal stents (FCSEMSs) represented the first alternative to DPPSs. Their larger diameter allows better drainage of solid debris, with lower rates of occlusion [9,[37][38][39].…”
Section: Fully Covered Self-expandable Metal Stentsmentioning
confidence: 99%
“…The overall LAMS-related AEs rate treating WOPN appears difficult to evaluate because of the lack of data uniformity among published series. The main AEs reported are migration/dislodgement of the stent (2.6-10.6%), occlusion (0.9-8.7%), bleeding (0.7-5.5%) and perforation (0-1.3%) [39].…”
Section: Clinical Practice With Lamssmentioning
confidence: 99%
See 1 more Smart Citation